2009
DOI: 10.1097/smj.0b013e3181bfdc67
|View full text |Cite
|
Sign up to set email alerts
|

Mass Casualties from Acute Inhalation of Chlorine Gas

Abstract: Chlorine gas is a potent pulmonary irritant that causes acute damage in both the upper and lower respiratory tract. We suggest that inhaled steroids combined with nebulized sodium bicarbonate could be a safe and effective alternative for the treatment of symptomatic patients. Education of the public about the dangers of mixing of hypochlorite bleach with acidic cleaning agents is also very important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 12 publications
2
36
0
Order By: Relevance
“…Several examples pertaining to the use of Cl 2 as a chemical weapon and large-scale accidental exposures attributable to the derailment of trains transporting Cl 2 through populated areas have been documented (3,8,21,31,34). The potential for future incidents remains because of the demand for Cl 2 in multiple industrial processes (8).…”
mentioning
confidence: 99%
“…Several examples pertaining to the use of Cl 2 as a chemical weapon and large-scale accidental exposures attributable to the derailment of trains transporting Cl 2 through populated areas have been documented (3,8,21,31,34). The potential for future incidents remains because of the demand for Cl 2 in multiple industrial processes (8).…”
mentioning
confidence: 99%
“…All patients were treated with nebulized salbutamol, and 19 of 25 were also given inhaled budesonide and 4 mL of 3.75 % nebulized sodium bicarbonate solution. There was no difference in outcomes between the 19 treated with budesonide and sodium bicarbonate and the 6 who were not [15].…”
Section: Case Continuationmentioning
confidence: 73%
“…Physical exam findings vary depending on exposure severity but most commonly consist of wheezing, rales, decreased breath sounds, tachypnea, and increased work of breathing. In their 2009 study of 25 young, male soldiers exposed to chlorine gas on a military base, Cevik et al found that 48 % of patients had wheezing, rales, or decreased breath sounds [15]. In 2002, Güloğlu et al described a cohort of 106 people exposed to chlorine gas in Turkey, of which 28 % had abnormal pulmonary physical findings-primarily wheezing [17].…”
Section: Case Continuationmentioning
confidence: 99%
See 2 more Smart Citations